APPLICATION OF SPEAKING SKILLS WITH THE DISCUSSION METHOD THROUGH A COMMUNICATIVE APPROACH TO ELEMENTARY SCHOOL STUDENTS - Amiruddin Amiruddin; Noveria Fradila; Putri Pramestia Ningrum; Miftahul Jannah; Wirdania Nasution; Susanti Santi (Universitas Trunojoyo Madura, 2022)
This paper aims to determine how skilled students are in speaking through the discussion method with a communicative approach. This study used qualitative research methods. Because in this research we need observation, visual analysis, literature study as well as conducting interviews with informants. In this research, the most important thing we do is carry out direct observations related to the problem we are studying. Because with observation, we can see directly what is happening in the field according to the facts. Based on the results of observations, the application of the discussion method through a communicative approach to elementary school students is effectively used to cultivate students' speaking skills, because it triggers students to ask questions, have opinions and of course know many things that were previously unknown.